Clinical Implementation Study of Genetic Risk-Based Breast Cancer Screening - Tamm, Madli; Padrik, Peeter; Ojamaa, Kristiina; Paas, Anette; Lepland, Anni; Kruuv-Käo, Krista; Leitsalu, Liis; Sõber, Siim; Roht, Laura; Pajusalu, Sander; Kahre, Tiina; Padrik, Anna; et al. (Clinical breast cancer, 2025)
•Evaluated a genetic risk-based personalized breast cancer screening service model.•Utilized telemedicine, home-based testing, and questionnaire-based decision-making.•Clinical recommendations were given based on polygenic and monogenic risk.•Included young high-risk women in the national screening program.•Proposed service model has potential to enhance breast cancer screening programs. Breast cancer (BC) remains the most common type of cancer and the leading cause of cancer-related deaths in women despite the widespread screening programs and personalized treatment options. Current age-based screening programs are suboptimal missing high-risk young women. The “Be RIGHT with breast cancer risk management” (BRIGHT) study evaluated a genetic risk-based personalized BC screening service model in real-world healthcare settings, focusing on younger women excluded from standard screening. The BRIGHT study included 800 healthy Estonian women aged 35 to 49 using telemedicine and home-based testing. Participants underwent polygenic risk score (PRS) testing and based on the questionnaire those meeting the monogenic pathogenic variant (MPV) testing criteria were referred to clinical geneticists. All women received personalized genetic risk-based clinical recommendations, and if needed, referral to BC screening. Participants’ and healthcare professionals’ feedback was collected. 330 (41.3%) women with elevated polygenic risk received recommendations to start screening earlier than the current standard. 124 (15.5%) women were advised to begin BC screening immediately, among whom one was diagnosed with stage 0 cancer and one with a precancerous lesion. Of the 90 participants completing MPV testing, four (4.4%) were MPV-positive. Feedback indicated high satisfaction with the digital approach and a clear understanding of results and recommendations. The study demonstrated the feasibility and acceptability of a personalized genetic risk-based BC screening model. It has the potential to enhance BC screening programs, particularly for younger women and those at higher genetic risk, while avoiding unnecessary interventions for low-risk individuals. Breast cancer (BC) remains the most common malignant tumor site and the leading cause of cancer-related deaths in women despite the wide availability of screening programs and personalized treatment options. The BRIGHT study tested a genetic risk-based personalized BC screening service model in women younger than 50 years, using telemedicine and home-based testing. Participants underwent polygenic risk score and monogenic pathogenic variant testing. This type of screening model demonstrated feasibility, clinical utility, and acceptability. It has the potential to enhance BC screening programs, particularly for younger women and those at higher genetic risk, while avoiding unnecessary interventions for low-risk individuals.